6. Erythrocyte Profile of Male Piglet Aged 31-Day Old (Sus scrofa domestica) in the Laboratory Animal Management Unit IPB University - Gunanti Gunanti; Damiana Rita Ekastuti; Dwi Utari Rahmiati; Muhammad Fajrul Falah; Erwin Erwin (Jurnal Medika Veterinaria, 2021)
Domestic pig (Sus scrofa domestica) is well known as animal that used frequently as a research animal due to their similarity to human both in  terms of anatomy and physiology. Information regarding  standard value of domestic piglet’s hematology in Indonesia are still limited. The aim of this study was to obtain erythrocyte profiles of domestic piglets in Animal Laboratory and Research Unit, Bogor Agricultural University. The results of this study are expected to be used as an erythrocyte profiles reference of domestic piglets in Indonesia. Blood samples were collected from six male piglets in Animal Laboratory and Research Unit, Bogor Agricultural University through auricular vein, then the samples were put into a vaccuum tube containing anticoagulant (K3EDTA) for further test using hematology analyzer. The parameters used in this study consist of erythrocyte count, hemoglobin concentration, hematocrit, and erythrocyte indices. Data were analyzed descriptively in the form of mean ± standard deviation (minimum–maximum). The results of this study showed that the average of erythrocyte counts were 6,42 ± 1,03 millions/µL with 8,30 ± 1,51 g/dl hemoglobin concentration, hematocrite 29,80 ± 5,10%, MCV 46,47 ± 1,62 fL, MCH 12,83 ± 0, 65 pg, MCHC 27,75 ± 0,71 g/dL, and RDW 28,87 ± 3,86%.